Museomics analyses inform about Channichthys icefish species diversity - Garmann-Aarhus, Benedicte; Nikolaeva, Ekaterina; Desvignes, Thomas; Straube, Nicolas; Matschiner, Michael (bioRxiv, 2024)
The rapid diversification of notothenioid fishes in the waters surrounding the Antarctic continent is a prime example of the process of adaptive radiation. Within around 10 million years, Antarctic notothenioids have diversified into over 100 species with a broad range of lifestyles and ecological adaptations. However, the exact number of species within this radiation has long been unclear. Particularly challenging is the taxonomy of the genus Channichthys, for which between one and nine species have been recognized by different authors. The putative species from this genus are known from a limited number of representative specimens, of which most were sampled decades ago. Here, we investigated the mitochondrial genomes of museum specimens representing the four recently recognized species Unicorn Icefish (C. rhinoceratus), Red Icefish (C. rugosus), Sailfish Pike (C. velifer), and Charcoal Icefish (C. panticapaei), complemented by morphological analyses. All analyzed specimens were collected in the 1960s and 1970s and fixed in formaldehyde, and their DNA has thus been heavily degraded. Applying ancient-DNA protocols for DNA extraction and single-stranded library preparation, we were nevertheless able to obtain sufficient endogenous DNA to reconstruct the mitochondrial genomes of one specimen of each species. These mitochondrial genome sequences were nearly identical for the three specimens assigned to Unicorn Icefish, Red Icefish, and Sailfish Pike, while greater mitochondrial divergence was observed for the Charcoal Icefish specimens. We discuss possible explanations of the contrast between these molecular results and the recognizable morphological variation found among the four species, and recommend that at least the Charcoal Icefish be included the list of valid icefish and notothenioid species.Competing Interest StatementThe authors have declared no competing interest.
Keywords: Sørishavet; fisker; genetisk analyse; marin biologi; morfologi; taksonomi; zoologi; økologi

Genomics of cold adaptations in the Antarctic notothenioid fish radiation - Bista, Iliana; Wood, Jonathan M. D.; Desvignes, Thomas; McCarthy, Shane A.; Matschiner, Michael; Ning, Zemin; Tracey, Alan; Torrance, James; Sims, Ying; Chow, William; Smith, Michelle; Oliver, Karen; et al. (Nature Communications, 2023)
Numerous novel adaptations characterise the radiation of notothenioids, the dominant fish group in the freezing seas of the Southern Ocean. To improve understanding of the evolution of this iconic fish group, here we generate and analyse new genome assemblies for 24 species covering all major subgroups of the radiation, including five long-read assemblies. We present a new estimate for the onset of the radiation at 10.7 million years ago, based on a time-calibrated phylogeny derived from genome-wide sequence data. We identify a two-fold variation in genome size, driven by expansion of multiple transposable element families, and use the long-read data to reconstruct two evolutionarily important, highly repetitive gene family loci. First, we present the most complete reconstruction to date of the antifreeze glycoprotein gene family, whose emergence enabled survival in sub-zero temperatures, showing the expansion of the antifreeze gene locus from the ancestral to the derived state. Second, we trace the loss of haemoglobin genes in icefishes, the only vertebrates lacking functional haemoglobins, through complete reconstruction of the two haemoglobin gene clusters across notothenioid families. Both the haemoglobin and antifreeze genomic loci are characterised by multiple transposon expansions that may have driven the evolutionary history of these genes.
Keywords: Sørishavet; fisker; marin biologi; zoologi

Xenobiotic metabolism and its physiological consequences in high-Antarctic Notothenioid fishes - Strobel, Anneli; Lille-Langøy, Roger; Segner, Helmut; Burkhardt-Holm, Patricia; Goksøyr, Anders; Karlsen, Odd André (Polar Biology, 2022)
The Antarctic ecosystem is progressively exposed to anthropogenic contaminants, such as polycyclic aromatic hydrocarbons (PAHs). So far, it is largely unknown if PAHs leave a mark in the physiology of high-Antarctic fish. We approached this issue via two avenues: first, we examined the functional response of the aryl hydrocarbon receptor (Ahr), which is a molecular initiating event of many toxic effects of PAHs in biota. Chionodraco hamatus and Trematomus loennbergii served as representatives for high-Antarctic Notothenioids, and Atlantic cod, Gadus morhua as non-polar reference species. We sequenced and cloned the Ahr ligand binding domain (LBD) of the Notothenioids and deployed a GAL4-based luciferase reporter gene assay expressing the Ahr LBD. Benzo[a]pyrene (BaP), beta-naphthoflavone and chrysene were used as ligands for the reporter gene assay. Second, we investigated the energetic costs of Ahr activation in isolated liver cells of the Notothenioids during acute, non-cytotoxic BaP exposure. In the reporter assay, the Ahr LBD of Atlantic cod and the Antarctic Notothenioids were activated by the ligands tested herein. In the in vitro assays with isolated liver cells of high-Antarctic Notothenioids, BaP exposure had no effect on overall respiration, but caused shifts in the respiration dedicated to protein synthesis. Thus, our study demonstrated that high-Antarctic fish possess a functional Ahr that can be ligand-activated in a concentration-dependent manner by environmental contaminants. This is associated with altered cost for cellular protein synthesis. Future studies have to show if the toxicant-induced activation of the Ahr pathway may lead to altered organism performance of Antarctic fish.
Keywords: Sørishavet; fisker; marin zoologi; marinbiologi

Allometric relationships of ecologically important Antarctic and Arctic zooplankton and fish species - Schaafsma, Fokje L.; David, Carmen L.; Kohlbach, Doreen; Ehrlich, Julia; Castellani, Giulia; Lange, Benjamin A.; Vortkamp, Martina; Meijboom, André; Fortuna-Wünsch, Anna; Immerz, Antonia; Cantzler, Hannelore; Klasmeier, Apasiri; et al. (Polar Biology, 2022)
Allometric relationships between body properties of animals are useful for a wide variety of purposes, such as estimation of biomass, growth, population structure, bioenergetic modelling and carbon flux studies. This study summarizes allometric relationships of zooplankton and nekton species that play major roles in polar marine food webs. Measurements were performed on 639 individuals of 15 species sampled during three expeditions in the Southern Ocean (winter and summer) and 2374 individuals of 14 species sampled during three expeditions in the Arctic Ocean (spring and summer). The information provided by this study fills current knowledge gaps on relationships between length and wet/dry mass of understudied animals, such as various gelatinous zooplankton, and of animals from understudied seasons and maturity stages, for example, for the krill Thysanoessa macrura and larval Euphausia superba caught in winter. Comparisons show that there is intra-specific variation in length–mass relationships of several species depending on season, e.g. for the amphipod Themisto libellula. To investigate the potential use of generalized regression models, comparisons between sexes, maturity stages or age classes were performed and are discussed, such as for the several krill species and T. libellula. Regression model comparisons on age classes of the fish E. antarctica were inconclusive about their general use. Other allometric measurements performed on carapaces, eyes, heads, telsons, tails and otoliths provided models that proved to be useful for estimating length or mass in, e.g. diet studies. In some cases, the suitability of these models may depend on species or developmental stages.
Keywords: Sørishavet; biomasse; dyreplankton; fisker; marin biologi; marin økologi; polarområdene; zooplankton

Abnormal gonads in the Antarctic toothfish (Dissostichus mawsoni Norman, 1937 [Perciformes: Nototheniidae]): the first record and histological description - Zhukova, Kristina A; Gordeev, Ilya I; Kuznetsova, Elena N (Polar Research, 2018)
This paper describes the morphology and histology of abnormal gonads in Antarctic toothfish (Dissostichus mawsoni) and the possibility of intersexuality and senescence of some individuals. Two old (approximately 25 years) and large (184–185 cm) specimenswith abnormal gonadswere caught in the Antarctic during commercial fishing for toothfish and studied using histological methods. Although D. mawsoni is well-known and extensively studied, this is the first study dealing with abnormal gonads in the species. The histological analysis revealed that the gonads of the first specimen contained both male and female germ cells (ovotestis), the testicular and ovarian tissues being separated by a thick layer of connective tissue. The female portion was composed of secondary vitellogenic oocytes, primary vitellogenic, cortical alveolar and primary growth oocytes, while the testes contained cysts of spermatogonia and primary spermatocyte. The gonads of the second specimen were small, filiform and showed massive growth of the connective tissue, which occupied almost the entire gonad; a few spermatogonia without visible cystswere found. This study extends our understanding of sexual development in Antarctic toothfish, documenting the possibility of long-term interruptions in the reproductive cycle of this species.
Keywords: Sørishavet; fisker; gonader; histologi; marin biologi; morfologi; oseanografi; reproduksjon

Ontogenetic changes in the feeding strategy of Lepidonotothen nudifrons (Pisces, Nototheniidae) off the South Shetland Islands and the Antarctic Peninsula - Blasina, Gabriela; Cazorla, Andrea Lopez; Antoni, Mariana Deli; Bruno, Daniel; Delpiani, Matías; Díaz de Astarloa, Juan Martín (Polar Research, 2017)
The diet and feeding strategy of Lepidonotothen nudifrons off the South Shetland Islands and the Antarctic Peninsula, as well as their variation in relation to ontogenetic stage (juvenile– adult) and sampling area, were determined by stomach contents analysis. Additionally, the trophic level of this species was estimated to determine its position within the Antarctic food web. Out of 247 specimens with prey in their stomachs, 144 were caught near the South Shetland Islands and 103 off the Antarctic Peninsula. Ontogenetic changes in the trophic ecology of L. nudifrons were observed in both areas and were mainly related to a decrease of copepods and an increase of euphausiids in the diet. The diet of juveniles from the South Shetland Islands was characterized by the dominance of calanoid copepods, followed by isopods and amphipods, whereas diet off the Antarctic Peninsula was dominated by amphipods and cyclopoid copepods. The diet in adults was dominated by amphipods and euphausiids in both areas. The specialization of individual predators on different prey types was observed when considering the whole population of L. nudifrons, but when ontogenetic stages were considered separately it showed a more mixed feeding strategy, with different dominant prey for each class. Although the trophic level increased with fish size, L. nudifrons can be classified as secondary consumer throughout its lifespan.
Keywords: Sørishavet; amfipoder; copepoder; euphausiacea; fauna; fisker; isopoder; marin zoologi; økosystemer

First record of humpback anglerfish (Melanocetus johnsonii) (Melanocetidae) in Antarctic waters - Orlov, Alexei M.; Orlova, Svetlana Y.; Volkov, Alexander A.; Pelenev, Dmitry V. (Polar Research, 2015)
The first record of the humpback anglerfish (Melanocetus johnsonii) in Antarctic waters (Ross Sea) is documented. Species identification is confirmed by the structure of the escal bulb and analysis of the mitochondrial cytochrome oxidase subunit I (COI) gene. This record extends the known range of M. johnsonii by more than 1000 nm to the south. The taxonomic status of Melanocetus species in Antarctic waters is discussed. Keywords: Melanocetus sp.; new record; taxonomy; distribution; Ross Sea; Antarctic.
Keywords: Rosshavet; Sørishavet; fisker; genetisk analyse; marin zoologi; taksonomi; zoogeografi

Dietary overlap in inshore notothenioid fish from the Danco Coast, western Antarctic Peninsula - Casaux, Ricardo; Barrera-Oro, Esteban (Polar Research, 2013)
We carried out a dietary overlap analysis between notothenioid species by examining the stomach contents of more than 900 specimens collected in a fish assemblage at the Danco Coast, western Antarctic Peninsula, in the summer of 2000. Prey reoccurrences among fish species were 32.2%, with krill Euphausia superba, salps and the gammaridean Prostebeingia longicornis the most reoccurring prey. The diet similarity between species pairs was lower than 55%, in accordance with similar fish assemblages in the South Orkney Islands, the South Shetland Islands and the Antarctic Peninsula. Whereas at those localities the higher prey overlap was between krill-feeding fish species, at the Danco Coast it was between Trematomus bernacchii and Lepidonotothen nudifrons, Notothenia coriiceps and Notothenia rossii, Notothenia coriiceps and Parachaenichthyis charcoti, and Trematomus newnesi and Notothenia rossii, which shared primarily gammaridean amphipods, algae, fish and krill, respectively. Krill is normally the main prey of fish in summer in inshore waters of the western Antarctic Peninsula, but its density in January/February 2000 was notably lower than in previous years. Therefore, at the Danco Coast, under conditions of krill shortage, most of the notothenioid species foraged more intensively on alternative prey, such as gammarideans, fish and algae. The difference between areas in the pattern of dietary overlap might be related to differences in prey availability between years and to the degree of competition for targeted prey. Keywords: Fish dietary overlap; notothenioid fish; Antarctic Peninsula.
Keywords: Sørishavet; fisker; forskning; krill; marin biologi; plankton; økosystemer

Adaptations and lifestyle in polar marine environments: a biological challenge for the study of fish evolution - Verde, Cinzia; Cocca, Ennio; de Pascale, Donatella; Parisi, Elio; di Frisco, Guido (Polar Research, 2004)
The climatic features of Antarctic waters are more extreme and constant than in the Arctic. The Antarctic has been isolated and cold longer than the Arctic. The polar ichthyofaunas differ in age, endemism, taxonomy, zoogeographic distinctiveness and physiological tolerance to environmental parameters. The Arctic is the connection between the Antarctic and the temperate-tropical systems. Paradigmatic comparisons of the pathways of adaptive evolution of fish from both poles address the oxygen-transport system and the antifreezes of northern and southern species, (i) Haemoglobin evolution has included adaptations at the biochemical, physiological and molecular levels. Within the study of the molecular bases offish cold adaptation, and taking advantage of the information on haemoglobin amino acid sequence, we analysed the evolutionary history of the ? and ? globins of Antarctic, Arctic and temperate haemoglobins as a basis for reconstructing phylogenetic relationships. In the trees, the constant physico-chemical conditions of the Antarctic waters are matched by clear grouping of globin sequences, whereas the variability typical of the Arctic ecosystem corresponds to high sequence variation, reflected by scattered intermediate positions between the Antarctic and non-Antarctic clades. (ii) Antifreeze (glyco)proteins and peptides allow polar fish to survive at sub-zero temperatures. In Antarctic Notothenioidei the antifreeze gene evolved from a trypsinogen-like serine protease gene. In the Arctic polar cod the genome contains genes which encode nearly identical proteins, but have evolved from a different genomic locus–a case of convergent evolution.
Keywords: Sørishavet; biokjemi; biologi; evolusjon; fauna; fisker; fysiologi; klima; miljø; zoogeografi; økosystemer

Residue determinants and sequence analysis of cold-adapted trypsins - Schrøder Leiros, Hanna-Kirsti; Willassen, Nils Peder; Smalås, Arne O. (Extremophiles, 1999)
The digestive enzyme trypsin is among the most extensively studied proteins, and its structure has been reported from a large number of organisms. This article focuses on the trypsins from vertebrates adapted to life at low temperatures. Cold-adapted organisms seem to have compensated for the reduced reaction rates at low temperatures by evolving more active and less temperature-stable enzymes. We have analyzed 27 trypsin sequences from a variety of organisms to find unique attributes for the cold-adapted trypsins, comparing trypsins from salmon, Antarctic fish, cod, and pufferfish to other vertebrate trypsins. Both the "cold" and the "warm" active trypsins have about 50 amino acids that are unique and conserved within each class. The main unique features of the cold-adapted trypsins attributable to low-temperature adaptation seem to be (1) reduced hydrophobicity and packing density of the core, mainly because of a lower (Ile + Leu)/(Ile + Leu + Val) ratio, (2) reduced stability of the C-terminal, (3) lack of one warm trypsin conserved proline residue and one proline tyrosine stacking, (4) difference in charge and flexibility of loops extending the binding pocket, and (5) different conformation of the "autolysis" loop that is likely to be involved in substrate binding.
Keywords: Sørishavet; biokjemi; fisker; marin biologi; mikrobiologi; polarområdene

Occurrence of Pseudoterranova decipiens (Nematoda) in fish from the Southeastern Weddell Sea (Antarctic) - Palm, Harry; Andersen, Karin; Klöser, Heinz; Plötz, Joachim (Polar Biology, 1994)
Eleven fish species from the Weddell Sea (Antarctic) were examined for infestation with anisakid nematodes. Two species of the genus Contracaecum and the sealworm Pseudoterranova decipiens were isolated from the liver and the body cavity of fish affected. Only two specimens of P. decipiens (1.4%) partly invaded the belly flaps. The following fish species were infested by P. decipiens at the given prevalences: Cygnodraco mawsoni (74.4%), Trematomus scotti (23.2%), Pagetopsis maculatus (10.0%), Cryodraco antarcticus (7.1%), Trematomus lepidorhinus (3.0%), and Dolloidraco longedorsalis (2.7%). All of these, except Trematomus scotti, are new host records. Chaenodraco wilsoni, Chionodraco myersi, Gerlachea australis, Racovitzia glacialis and T. eulepidotus were not infested. The reasons for low prevalence and intensity of infestation are seen in the difficulties of P. decipiens in completing its benthic life cycle in the Weddell Sea environment, in the absence of shallow coastal waters due to the floating shelf-ice. Cygnodraco mawsoni is a crucial intermediate host, without which completion of the parasite life cycle might not be possible. In order to clarify the taxonomical position of Antarctic Pseudoterranova, morphological comparisons with specimens of P. decipiens from the German and Norwegian coast were made using scanning electron microscopy. Results revealed no differences; hence, all specimens studied belong to the same species P. decipiens.
Keywords: Sørishavet; Weddellhavet; biodiversitet; fisker; marin biologi; økologi

Subantarctic and Antartic fishes - Nybelin, Orvar (Hvalfangstmuseet, 1951)
Keywords: Brategg ekspedisjon; Sørishavet; ekspedisjoner; fisker; forskning; iktiogeografi; magellanstredet; zoologi

Some new and remarkable leeches from the Antarctic seas - Brinkmann, August (Dybwad, 1948)
Keywords: Bouvetøya; Norvegia ekspedisjonen; Sørishavet; fisker; igler; marin biologi